The prognostic value of the Barthel Index for mortality in patients with COVID-19: A cross-sectional study - Wang, Erchuan; Liu, Ao; Wang, Zixuan; Shang, Xiaoli; Zhang, Lingling; Jin, Yan; Ma, Yanling; Zhang, Lei; Bai, Tao; Song, Jun; Hou, Xiaohua (Frontiers in Public Health, 2023)
This study aims at analyzing the association between the activity of daily living (ADL) and corona virus disease (COVID-19) and the value of Barthel index in predicting the prognosis of the patients. This study included 398 patients with COVID-19, whose ADL at admission to hospital were assessed with the Barthel index, and the relationship between the index and the mortality risk of the patients was analyzed. Several regression models and the decision tree were established to evaluate the prognostic value of the index in COVID-19 patients. The Barthel index of the deceased patients was significantly lower than the discharged (median: 65 vs 90, P < 0.001) and its decrease indicated an increased risk of mortality in the patients (P < 0.001). After adjusting for age, gender, temperature, pulse, respiratory rate, mean arterial pressure, oxygen saturation, etc. in the models, the Barthel index can still independently predict the prognosis (OR=1.236; 95% CI: 1.147-1.332). The decision tree showed patients with Barthel index below 70 have higher mortality (33.3-40.0%) while those above 90 are usually discharged (mortality: 2.7-7.2%), implying Barthel index is of great prognostic value for mortality in COVID-19 patients.